Integrated SPECT-MRI for enhanced stratification and early treatment response assessment in glioma. (31st January 2018) - Short, Susan; Hutton, Brian; Ottobrini, Luisa; De Francesco, Irene; Fiorini:, Carlo
Abstract: BACKGROUND: Personalised treatment based on individual tumour biology tracked over time is an important goal to improve outcomes in glioma. Imaging biomarkers have the potential to permit individualization by defining heterogeneous biology in 3D space and tracking response. To optimize application of this approach, biological readouts need to be aligned with high quality anatomical information. The INSERT consortium seeks to address this unmet need using simultaneous multi-tracer SPECT and MRI. AIM: Design and build a multi-modality imaging tool to allow simultaneous SPECT-MR assessment and read-out of multiple tumour biology biomarkers in patients with glioma. METHODS: A fully MRI compatible SPECT imaging system was designed for i) pre-clinical and ii) clinical applications. In both systems the SPECT imaging frame is inserted to the bore of a standard MRI scanner and can be moved between scanners. Novel components of the system include: unique MR compatible slit-slat collimator design, hand-built in precision-cut tungsten, high-resolution detection modules with customized SiPM readout, housed in a robust, 3D-printed unit that can be aligned with MR imaging isocentre to scan the whole brain. To develop optimized applications of this system, pre-clinical experiments were undertaken to assess the utility of novel SPECT tracers with MR imaging in orthotopic (U251) glioma models. RESULTS: The pre-clinical and clinical INSERT systems have been constructed and early feasibility testing is ongoing. In orthotopic models, SPECT combined with MRI is a promising approach to early response assessment that is highly correlated with bioluminescence imaging, autoradiography, PET and histology. A protocol for early assessment of the same biomarkers in glioma patients is agreed and will recruit in 2017. CONCLUSION: There remains a significant unmet need for better biological readouts of tumour response in glioma. The application of multi-modality imaging with the advanced technology and practical advantages of INSERT delivers novel opportunities in this setting.